1988
DOI: 10.1101/gad.2.12a.1677
|View full text |Cite
|
Sign up to set email alerts
|

A link between cell movement and gene expression argues that motility is required for cell-cell signaling during fruiting body development.

Abstract: Nonmotile mutants of Myxococcus xanthus (Myxobacterales) failed to execute the morphogenetic movements required to shape a fruiting body. In addition, nonmotile mutants produced very few spores when plated for fruiting body development at cell densities appropriate for wild-type cells. At higher initial cell densities, the proportion of nonmotile cells that sporulate increased, indicating that one important function of motility in fruiting body development is to increase the local cell density. However, even a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
98
0

Year Published

1991
1991
2015
2015

Publication Types

Select...
5
4

Relationship

3
6

Authors

Journals

citations
Cited by 86 publications
(99 citation statements)
references
References 20 publications
1
98
0
Order By: Relevance
“…1 and 2). Within aggregates, the local C-factor concentration would be expected to increase with cell density and with the increased efficiency of cell-to-cell C-factor transmission (9,10).…”
Section: Resultsmentioning
confidence: 99%
“…1 and 2). Within aggregates, the local C-factor concentration would be expected to increase with cell density and with the increased efficiency of cell-to-cell C-factor transmission (9,10).…”
Section: Resultsmentioning
confidence: 99%
“…The direction of movement of a chain is determined by the cell at the leading end of the chain and is conveyed from cell to cell by the end-to-end contacts. At the high cell density, cells tend to stay in side-by-side contact with each other (21,23,24). Cell movement in chains may create alignment of neighboring cells, thus giving rise to the formation of secondary chains, which are associated with the initiating chains by the lateral side-by-side contacts.…”
Section: Discussionmentioning
confidence: 99%
“…The C-signal induces aggregation and sporulation in a concentration-dependent manner, i.e., intermediate level aggregation is induced and at high levels sporulation is induced (13)(14)(15). C-signal transmission occurs by a contactdependent mechanism (12) that involves end-to-end contacts between cells and fails when cells are unable to make these even though they are able to make side-by-side contacts (21)(22)(23)(24).…”
mentioning
confidence: 99%
“…However, the aggregation, sporulation, and developmental gene expression of a csgA mutant is rescued by codevelopment with wild-type (wt) cells or by addition of purified C factor at 1 nM (5,6). Rescue by wt cells requires the motility of both cell types (17,18). It has been suggested that movement establishes specific contacts between cells (thought to be end-to-end contacts) that are required for intercellular C-factor signal transmission (19,20).…”
mentioning
confidence: 99%